Peran PT. Gudang Garam tbk. dalam Mengembangkan “New Tourism” Melalui Konser Musik di Surabaya - Adam, Brian; Rossalina, Gazella; Dimas, Paskalis; Yuliana, Putri (Global and Policy Journal of International Relations, 2013)
ABSTRACTIn Global tourism, any issue can be change and growth easily. Music concert easily held in Indonesia, especially in Surabaya it is becoming new tourism. To be one of the new program for promoting tourism in indonesia, PT Gudang Garam (tobacco corporation) being greater promotor to promote the program. And that program must support for tobacco product too. This paper will explain that PT. Gudang Garam can explore “new tourism” in Surabaya on 2007 – 2010. This paper start with the history of sponsorship Gudang Garam ini music concert, and the types of developing music sponsorship also continue with table of comparation tourism in Surabaya and finally there are result for that activities. This program can explain how cigarrette corp still get less contribution from local goverment.Keywords: “New Tourism”, Surabaya, Gudang Garam, Tourism, Music Sponsorship.DOI:https://doi.org/10.33005/jgp.v1i01.2014